Evaluation of dermal collagen stained with picrosirius red and examined under polarized light microscopy - Coelho,Polyana Galvão Bernardes (2018)
Abstract: The special picrosirius red staining highlights the natural birefringence of collagen fibers when exposed to polarized light. The results from birefringence allow to evaluate the organization of the collagen fibers in the tissues. The authors intend to elucidate all steps to obtain and capture images of histological sections stained with picrosirius red and evaluated under polarized light microscopy, as well as possible artefacts that may occur.